Microbial volatile fongerprints : potential use for soil / water diagnostics and correlation with traditional microbial parameters - Bastos , A. C. (Cranfield University, 2007)
This project used an electronic nose (E-nose) system composed of an array of 14 non- specific conducting polymer sensors for soil and water diagnostics, based on qualitative microbial volatile production patterns. It tested the feasibility of using soil microbial volatile fingerprints for detecting and monitoring changes in microbial activity in three soils, as a response to key environmental factors such as temperature (16, 25, 37°C), water potential (-0.7, -2.8 MPa), and nutrient (glucose and wheat straw) inputs. It also investigated their potential use for atrazine detection when applied to soil at usual field application rates (2.5 ppm) as well as for monitoring its bioremediation using the white-rot fungus Trametes versicolor (R26), for up to 24 weeks. Furthermore, statistical correlations were investigated between soil volatile profiles and traditional microbial parameters for characterising microbial communities and their metabolic activities such as respiration, dehydrogenase (DHA) and laccase (LAC) activities, bacterial and fungal colony counts and fungal community structure under different soil conditions. Finally, this study explored the potential of microbial volatile production patterns for monitoring the activity and differentiation of two Streptomyces species (S. aureofaciens A253 and S. griseus A26) in potable water and in soil, as well as the production of geosmin in both environments. Data in this research has demonstrated that the production of volatile organic compounds (VOC) in soil is likely to arise from microbial metabolism. The E-nose was able to detect variations in the patterns of volatile production from soil according to treatments, functioning as indicators of shifts in microbial activity and community structure. The potential for discrimination between soil types in relation to environmental factors and nutrient addition has been demonstrated for the first time using principle component analysis (PCA). Significant (p<0.05) correlations were also found between soil volatile patterns (through PC1) and traditional soil microbial parameters. The close relationship (r>0.80) between PC1 and soil respiration was particularly relevant, since it indicates that microbial volatile fingerprints, similarly to respiration, respond quickly to changes in soil conditions. The sensor array was also able to detect Streptomyces activity and differentiation as well as discriminate AC Bastos (2007) Soil & water volatile fingerprints between bacterial species at different concentrations in potable water and in soil. Using this approach, the presence of geosmin was detected in water at 0.5 ppb (below its human odour threshold detection, OTD) and in soil at 100 ppb (OTD not established). This study has, therefore, demonstrated that an E-nose can be employed as a rapid, sensitive, reproducible and non-invasive tool for characterising changes in soil environmental conditions, as well as for monitoring key soil processes such as organic matter decomposition and atrazine degradation. It also suggests that this approach can complement, and perhaps replace, some of these methods for a quick and routine evaluation of the impact of environmental factors on soil microbial communities. Furthermore, this study showed that an E-nose can also be employed for assessing Streptomyces activity and detecting geosmin production at an early stage in water and soil.